Antimicrobial peptide CAMA‐syn expressed in pulmonary epithelium by recombination adenovirus inhibited the growth of intracellular bacteria. (28th January 2020) - Yue, Shuohao; Jie, Jing; Xie, Lilan; Li, Yi; Zhang, Junlin; Lai, Xiaojing; Xie, Jumin; Guo, Xiaohong; Zhai, Yi
Abstract: Background: Intracellular bacteria, especially Mycobacterium tuberculosis, are important pathogenic microorganisms that endanger human health. Purified and synthesized cecropin A‐magainin 2 (CAMA‐syn) can exhibit a higher antibacterial activity and lower cytotoxicity. To enhance such antimicrobial potential, it would be desirable to deliver CAMA‐syn expressed in lung epithelial cells by an adenovirus vector using gene therapy. Methods: A549 cells in vitro and lung epithelial cells in vivo were used to express CAMA‐syn by transducing recombinant adenovirus Ad‐SPC‐CAMA/GFP, and the expression of CAMA‐syn was determined by a reverse transcriptase‐polymerase reaction (RT‐PCR) and immunofluorescence. The antimicrobial activity in cells was investigated by colony‐forming rate and growth curve. Forty Kunming mice of a Bacillus Calmette‐Guerin (BCG) infection animal model were randomly divided into three groups: adenoviruses delivery of Ad‐SPC‐CAMA/GFP, Ad‐CMV‐CAMA/GFP and empty‐virus Ad‐CMV‐GFP. The expression of CAMA‐syn in mice was confirmed by RT‐PCR and immunofluorescence. After tracheal injection of adenoviral vector for 3 days, lungs from the mouse model were extracted and homogenized for detection of colony‐forming efficiency. Results: CAMA‐syn expressed in lung epithelial cells A549 conferred antimicrobial activity against a series of bacteria, including Salmonella abortusovis and BCG. The results obtained in vivo showed that the colony‐forming rate of Ad‐SPC‐CAMA/GFP (74.54%) and Ad‐CMV‐CAMA/GFP (62.31%) transduced into mice was significantly lower than that of the control group. Conclusions: Lung epithelial‐specific expression of antimicrobial peptide CAMA‐syn mediated by adenovirus suppressed the growth of intracellular bacteria, providing a promising approach for the control of refractory intracellular infection.